Mistrz, błazen i ich międzykulturowa wspólnota. Śmiech na kulturowym pograniczu klasy szkolnej - Grzybowski, Przemysław Paweł (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The aim of these reflections is to verify the thesis concerning establishment of the community of laughter as one of the factors supporting and empowering teachers in the process of resolving conflicts, seeking dimensions of dialogue, and achieving compromise in the classroom (perceived as a cultural borderland).
Keywords: laughter; cultural borderland; cross-cultural education; teachers; classroom